The effect of GW9508 on cytotoxicity and gene expression of P53 in C118 cell line - Molaie, Hamidreza; Entezari, Maliheh (Archives of Advances in Biosciences, 2021)
Introduction: As one of the most common and invasive brain tumors, glioblastoma which originates in the nervous tissue of the brain has remained a therapeutic challenge given low success of conventional therapies. Small molecules including GW9508, due to their different roles in signaling and intracellular pathways and the production and increase of oxidative stress of mitochondrial origin, can cause cells to progress to apoptosis, also known as a cost-effective pharmacological factor. Therefore, in the present study, the anticancer and cytotoxic effects of GW9508 on A549 class lung cancer cells were investigated. Materials and Methods: In this experiment, the cell line (C118) was firstly cultured in DMEM culture medium containing 10% FBS and then treated with different concentrations of GW9508. MTT assay was used to determine IC50 and compare the viability of treated cells with different concentrations of GW9508 on days 1, 3, and 5 in the control group. To evaluate the effect, the qRT-PCR test was used with the IC50 concentration on the induction of apoptosis and expression of the P53 gene. Results: The results showed that GW9508 significantly reduced the viability and proliferation of C118 cells in a dose- and time-dependent manner (P <.05). Morphological changes such as reduction of chromatin density and cell rotation were also observed in the cells. Also, molecular results showed that GW9508 was able to increase the expression of the P53 gene. Conclusions: The GW9508 small molecule induces cell death in glioblastoma cancer cells by reducing cell viability and increasing P53 gene expression. As a result, it has therapeutic potential to induce cell death in cancer cells and to treat cancer.